2017
DOI: 10.7860/jcdr/2017/25798.10321
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Trichoblastoma of Nose: An Unusual Occurrence

Abstract: Nevus sebaceus of Jadassohn is a congenital tumour affecting the scalp and face. It is usually presented as a pigmented patch or plaque. It is a complex cutaneous hamartoma which involves pilosebaceous follicle, epidermis and adnexal structures. Tumours that arise from nevus sebaceous are basal cell carcinoma, syringocystadenoma papilliferum, trichoblastoma and hidradenoma. The progression and frequency of the tumour increase with the age. Here we present a case of pigmented trichoblastoma over the external no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…According to our knowledge, our case corresponds to the third case of nasal melanotrichoblastoma reported in literature [2,7]. The first case, described by Kamat et al, [2] was reported in a 50-year-old man with a 4.5cm mass over the tip of the nose that slowly enlarged over the course of 6 years.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…According to our knowledge, our case corresponds to the third case of nasal melanotrichoblastoma reported in literature [2,7]. The first case, described by Kamat et al, [2] was reported in a 50-year-old man with a 4.5cm mass over the tip of the nose that slowly enlarged over the course of 6 years.…”
Section: Discussionsupporting
confidence: 53%
“…The first case, described by Kamat et al, [2] was reported in a 50-year-old man with a 4.5cm mass over the tip of the nose that slowly enlarged over the course of 6 years. The second case, presented by Sathyaki et al, [7] was described in a 65-year-old Korean woman with a 1cm mass on the right side of the nosethat had been slowly enlarging over the course of 1 year. Comparing these clinical findings with our case demonstrate a relatively similar age of onset in the early to middle-aged adult years.…”
Section: Discussionmentioning
confidence: 97%
“…16 On histological examination, trichoblastoma shows small cells of round to oval morphology, grouped and separated by a fibrous stroma, in a stratified squamous epithelium and areas of necrosis with calcification. 24 Syringocystadenoma papilliferum is a neoplasia of the apocrine and eccrine sweat glands and manifests as isolated patches or as multiple nodules containing vesicles or exudate. 16 Histopathologically, the SCAP is characterized as an apocrine adnexal tumor with papillary projections and cystic ducts, which are covered by columnar or cuboidal cells with basophilic cytoplasm, often having a connection with the epidermis.…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…2 The differentiation relies on the presence of a myxoid stroma in addition to retraction of the stroma around the basaloid cell clusters, findings typical of basal cell carcinoma. 24 Regarding the genetic perspective, several studies have indicated a relationship between the appearance of nevus sebaceous, alone or as a multisystemic syndrome, and mutations in the HRAS, KRAS, and NRAS genes, so that the amino acid glycine is replaced by the amino acid arginine, which in turn leads to activation of the MAPK and PI3K-AKT pathways, 7,16 with a consequent increase in cell proliferation in mutated cells, 6,7 which was confirmed through the genetic analysis of blood cells and tissues from unaffected areas, corroborating the theory of genetic mosaicism. 15,25 Table 2 below depicts the most recurrent neoplasms in medical literature associated with nevus sebaceous.…”
Section: Histopathological Findingsmentioning
confidence: 99%